Uma proposta de implementa??o do multiplexador do sistema ISDB-TB - Ferreira, Juliano Silveira (2009)
The digital TV promises to revolutionize the way how we watch tv. Better images quality, new reception forms, the interactivity possibility, and more programs options are some of the new offered possibilities. New theories and technologies use, and tools were necessary to become those possibilities a reality. This paper offers an initial reference to those who want to start their researches on digital TV, to understand its functioning, and how those new possibilities are implemented. Beyond this, it is proposed an implementation model of an important equipment into the digital transmission system, that is the multiplexer. The used technologies are also shown for that. Those are important references, since the digital TV rules offer information on what the multiplexer must perform, but there are not technologies reference, which can be used for its implementation. The digital TV introduction in Brazil and other countries adoption in the same standard offer a great industry and Brazilian Academy development opportunity The present study aims to offer a reference and motivation, so that it happens.